2006
DOI: 10.1016/j.ssc.2006.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mn substitution on the delicate balance between structure and properties of Gd1.4Ce0.6Sr2RuCu2O10

Abstract: Some new members of a Ruthenocuprate (2212) series have been synthesized by Mn substitution for Ru in Gd 1.4C e0.6Sr2RuCu2O10 . Characterisation by XRD phase analysis followed by Rietveld refinement has been carried out. IR spectroscopy studies and Rietveld refinements are consistent with substitution of Mn at Ru site. XRD studies indicate changes in structural features on substitution including a significant change in lattice parameter for a very low substitution level (1mole% of Ru). The pristine compound sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…When Mn atom is doped at the Ca sites, it would interact with the small spins of Cu atoms in the CuO 2 planes. 6,15,16 The doped Mn-atoms are expected to suppress the inter-CuO 2 planer electronic correlations and would be helpful in understanding their role in the mechanism of high T c superconductivity. In high temperature superconductors, the fluctuation induced conductivity above the superconducting transition temperature (T c ) is important for the study of order parameter fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…When Mn atom is doped at the Ca sites, it would interact with the small spins of Cu atoms in the CuO 2 planes. 6,15,16 The doped Mn-atoms are expected to suppress the inter-CuO 2 planer electronic correlations and would be helpful in understanding their role in the mechanism of high T c superconductivity. In high temperature superconductors, the fluctuation induced conductivity above the superconducting transition temperature (T c ) is important for the study of order parameter fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Important results have been obtained in this way, although sometimes the attempts to correlate results from different groups have led to contradictions [7][8][9][12][13][14][15][16][17]. A second approach is the study of chemically altered compounds, where by proper chemical substitutions one can control relevant parameters that affect the sample's properties and, in this way, get a better understanding of the mechanisms involved in it [18][19][20][21][22][23][24][25][26][27]. This second approach is particularly interesting for exploring the possible microscopic coexistence of superconductivity and magnetic order in the ruthenocuprate family.…”
Section: Introductionmentioning
confidence: 99%
“…which could modify the spins of immediate copper atoms. [14][15][16] The doping effect of Mn on the superconductivity of Cu 0.5 Tl 0.5 Ba 2 Ca 2 Cu 3 O 10Ày has not been reported so far although Mn doping causes a series of interesting phenomena in NdCaCuO, LaSrCuO, and YBaCuO. [17][18][19][20][21][22] For example, Mn doping in NdCaCuO causes an orthorhombicto-tetragonal structure transition, and significantly suppresses T c (0) and the superconducting volume fraction.…”
mentioning
confidence: 99%
“…19 Mn doping in LaSrCuO also induces a spin-compensated state on some length scale which decreases the Meissner volume, along with a coexistence of superconductivity and ferromagnetism. 15,[18][19][20] The critical temperature of YBaCuO has been decreased drastically after Mn doping. XRD measurements showed that the structure of the YB 2 Cu 4 O 8 phase was also largely affected even at low manganese-substitution The pellets of thallium mixed material were prepared under 3.8 tons/cm 2 pressure.…”
mentioning
confidence: 99%